Learning to Live with COVID-19 in Nepal: A Unique Experience - Singh, Yogendra P (Journal of Institute of Medicine Nepal, 2020)
Corona Virus Disease-2019 (COVID-19) is a global viral respiratory outbreak, known to everyone in society. Nepal is not an exception for this pandemic and we are learning how to live with COVID-19. The pandemic has changed vigorously our daily activities affecting every aspects of the society. In low–middle income countries like ours, we don’t have definite answer to deal with the pandemic, rather we are learning how to live amid COVID-19. We are experiencing something new every day. Despite so many limitations, we need to learn to live with COVID-19.